Development of Risk Assessment in Electricity Distribution Based on Green Supply Chain Operational Reference (GREEN SCOR) - Pramesti Sri Indraswari; Erwin Widodo (Publikasi Indonesia, 2025)
Sustainability, particularly in green supply chains, has become a global priority. Operational decisions that prioritize environmental concerns significantly affect a company's risk profile, making risk management in green supply chains crucial for operational sustainability and regulatory compliance. To align with the Net Zero Emissions (NZE) 2060 vision, electricity distribution must adopt risk assessment practices based on the Green Supply Chain Operations Reference (Green SCOR) framework. This framework incorporates environmental considerations into each business process. Using the House of Risk (HOR) method, risk agents and responses are identified and mapped, with risk impact assessed by experts. The HOR method ranks risks in two phases: Phase 1 calculates the Aggregate Risk Potential (ARP) based on the relationship between risk agents and events, and Phase 2 ranks them from highest to lowest. The risk assessment suggests mitigation strategies in line with Green SCOR, such as adopting green industry standards with suppliers and ensuring flexible contracts. Some risks, however, still require existing responses, like compliance with local content requirements (TKDN) and transitioning to electric vehicles. This process selects risk mitigation strategies based on available resources and organizational capability.